Pengaruh Model Pembelajaran Kooperatif Tipe Tems Games Tournamet (TGT) melalui Media Permainan Ludo terhadap Hasil Belajar Geografi Siswa Kelas XII IPS SMAN 1 Matur Kabupaten Agam - Fauziah, Suci; Afdhal, Afdhal (YASIN, 2023)
This research aims to determine whether there is an influence of the Tems Games Tournament (TGT) type cooperative learning model through the media of the ludo game on the geography learning outcomes of class XII IPS students at SMAN 1 Matur, Agam Regency. This type of research is quantitative research using experimental methods (Quasi Experimental Design) with a research design in the form of a nonequivalent Pretest-Posttest Control Group. The sampling technique used Purposive Sampling technique with a sample size of 56 students divided into control class, namely class XII IPS 2 and experimental class, namely class XII IPS 3 with a total of 28 students in each class. The data in this research are learning outcomes tests in the form of Pretest and Posttest. The data analysis techniques used are normality test, homogeneity test, hypothesis test, and N-Gain test. The results of this research showed that the average posttest score for the experimental class was 86.25 and the control class was 74.36. In the experimental class, an increase in N-Gain knowledge was obtained by 0.725, which is in the high category. Meanwhile, in the control class, an increase in N-Gain knowledge was obtained by 0.431, which is in the medium category. The results of the analysis for both classes used the t test at a significant level of α = 0.05 and obtained tcount = 5.847 and ttable = 1.674 so that tcount > ttable, then H0 was accepted, meaning that there was an influence of the Teams Games Tournament (TGT) Type Cooperative Learning Model through the Ludo Game Media on Geography Learning Results for Class XII IPS Students at SMAN 1 Matur, Agam Regency.